2006
DOI: 10.1037/1524-9220.7.4.212
|View full text |Cite
|
Sign up to set email alerts
|

The normative Male Alexithymia Scale: Measurement of a gender-linked syndrome.

Abstract: This series of studies assessed the psychometric properties of the Normative Male Alexithymia Scale (NMAS), a brief scale designed to assess normative male alexithymia. Exploratory and confirmatory factor analyses using separate samples (n ϭ 248 and 467, respectively) indicated that the NMAS consisted of a single 20-item factor. Scores on the NMAS displayed very good internal consistency (␣ ϭ .92-.93), and test-retest reliability (r ϭ .86 -.91) over a 1-2 month period. Results of analyses of gender differences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
117
0
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 72 publications
4
117
0
2
Order By: Relevance
“…These findings may be due to the way that the items in the DSHI were worded, specifically, using the phrase, "intentionally (on purpose)." It has been suggested that, as a result of masculine gender socialization, men may struggle to articulate their thoughts and feelings (Levant et al, 2003;Levant et al, 2006;Real, 1999), specifically around self-harm behaviors. As such, some men, as a result of masculine gender socialization, may engage in self-harm, but do so impulsively (not "on purpose") and, as such, would not have reported this on the study's survey.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These findings may be due to the way that the items in the DSHI were worded, specifically, using the phrase, "intentionally (on purpose)." It has been suggested that, as a result of masculine gender socialization, men may struggle to articulate their thoughts and feelings (Levant et al, 2003;Levant et al, 2006;Real, 1999), specifically around self-harm behaviors. As such, some men, as a result of masculine gender socialization, may engage in self-harm, but do so impulsively (not "on purpose") and, as such, would not have reported this on the study's survey.…”
Section: Discussionmentioning
confidence: 99%
“…Adherence to masculine norms is linked to features of emotional dysregulation in men, including alexithymia (Cusack, Deane, Wilson, & Ciarrochi, 2006;Jakupcak, Osborne, Michael, Cook, & McFall, 2006;Levant et al, 2003;Levant et al, 2006) as well as fear and purposeful avoidance or suppression of vulnerable emotions (e.g., sadness and depression, anxiety or fear; Jakupcak, Salters, Gratz, & Roemer, 2003;Wide, Mok, McKenna, & Ogrodniczuk, 2011), and avoidance of negative affect (Green & Addis, 2012). This literature suggests that some men, as a function of masculine norms, may struggle to experience and express a wide array of negative emotions.…”
mentioning
confidence: 99%
“…Scores on the NMAS displayed evidence of internal consistency (α = .92 for men) and test-retest reliability (r = .91 for men) over a 1 to 2 month period (Levant et al, 2006). Observations of gender differences, relations of the NMAS with other instruments, and its incremental validity in predicting masculinity ideology provide evidence supporting scale interpretations.…”
Section: Normative Male Alexithymia Scale (Nmas)mentioning
confidence: 67%
“…The NMAS (Levant et al, 2006) is a 20-item, unidimensional inventory in which participants answer questions about their own experience of emotions using a Likert-type format (1 = strongly disagree; 7 = strongly agree), with higher scores indicating higher levels of alexithymia. Scores on the NMAS displayed evidence of internal consistency (α = .92 for men) and test-retest reliability (r = .91 for men) over a 1 to 2 month period (Levant et al, 2006).…”
Section: Normative Male Alexithymia Scale (Nmas)mentioning
confidence: 99%
See 1 more Smart Citation